MARINE MICROBES: SOURCES OF NATURAL BIOACTIVE COMPOUNDS FOR APPLICATION IN PHARMACEUTICAL RESEARCH - Mien, Pham Thi; Ha, Dao Viet (Vietnam Journal of Marine Science and Technology, 2017)
Marine microbiology is currently the topic that scientists worldwide are interested in with the aim of searching for bioactive substances. In addition to the inherent microorganisms in marine sediments, other marine lives - associated microorganisms have recently been more invested and important achievements of pharmaceutical research applications have been gained in the last few decades. In this article, we review the milestones in the process of looking for “drugs from the sea” and focus on remarkable results in marine microbes associated with invertebrate and their potential application in drug investigation from the latest published papers in prestigious international journals.